Thermosetting maleimide resin composition

By using a combination of a bismaleimide compound, a thermosetting resin and a reaction accelerator, the molecular structure and reaction process of the resin are optimized, and the problems of insufficient dielectric properties and insufficient heat resistance in the prior art are solved, and a resin composition with excellent dielectric properties, heat resistance and moisture resistance are realized.

CN119899528APending Publication Date: 2025-04-29SHIN ETSU CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411496725.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-10-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult to develop a resin that has excellent dielectric properties while maintaining heat resistance and moisture resistance, low melt viscosity during heating, and film-forming properties.

Method used

The thermoset maleimide resin composition containing a bismaleimide compound, a thermosetting resin and a reaction promoter is used to optimize the properties of the resin through specific molecular structures and reaction steps.

Benefits of technology

A cured product with low relative dielectric constant and dielectric loss tangent at high frequency, excellent dielectric characteristics, high glass transition temperature, low thermal expansion coefficient, and excellent heat resistance and humidity resistance at high frequency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899528A_ABST
    Figure CN119899528A_ABST
Patent Text Reader

Abstract

The invention provides a thermosetting maleimide resin composition. The thermosetting maleimide resin composition has a low melt viscosity when heated, a cured film that is a cured product thereof has excellent flexibility, a low relative dielectric constant and dielectric loss tangent, a high glass transition temperature, a low coefficient of thermal expansion, and excellent heat resistance and moisture resistance even after long-term placement. The thermosetting maleimide resin composition includes (A) a bismaleimide compound represented by formula (1) [Chemical Formula 1] # imgabs0 # (in formula (1), A represents a tetravalent organic group having a cyclic structure, B represents a divalent hydrocarbon group derived from a dimer acid skeleton, Q represents a divalent group having a fluorene skeleton or an indene skeleton, W is B or Q, n is 1-100, and m is 1-100. (B) a thermosetting resin having one or more maleimide group reactive functional groups selected from the group consisting of an alkenyl group, a maleimide group, an epoxy group, a cyanate group, a hydroxyl group, an acid anhydride group, a (meth) acryloyl group, and a thiol group; and (C) a reaction accelerator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermosetting maleimide resin composition. Background Art

[0002] In recent years, the next generation communication systems such as 5G (millimeter wave region of 26GHz to 80GHz) have become popular, and further, more advanced next generation communication systems such as 6G have begun to be developed. These communication systems strive to achieve higher speed, larger capacity, and lower latency communications than the current ones. In order to realize these communication systems, materials for high frequency bands of 3GHz to 80GHz are required, and as a noise countermeasure, transmission loss must be reduced.

[0003] Transmission loss is the sum of conductor loss and dielectric loss. To reduce conductor loss, the surface roughness of the metal foil used is required. On the other hand, since dielectric loss is proportional to the product of the square root of the relative dielectric constant and the dielectric loss tangent, it is required to develop insulating materials with excellent dielectric properties.

[0004] In addition, since printed circuit boards or electronic components using insulating materials require a reflow process when packaging, highly heat-resistant materials with a high glass transition temperature (Tg) are required.

[0005] Among them, insulating materials with excellent dielectric properties are particularly required in substrate applications. For example, reactive polyphenylene ether (PPE) resins are used in rigid substrates, and liquid crystal polymers (LCP) and modified polyimides (MPI) with improved properties are used in flexible printed circuit boards (FPCs).

[0006] Although these materials have excellent characteristics, it is also a fact that there are many problems. For example, although reactive PPE resin has excellent dielectric properties and high Tg, due to the brittleness of the cured product and poor operability, it is limited to the use of prepregs, etc. (for example, patent documentation 1). About LCP, multiple inventions such as base film or cover film of FPC that further high performance and LCP are disclosed (for example, patent documentation 2). However, since LCP is difficult to batch production, it has limitation in use, and there is also a part that needs to be improved in many aspects such as the adhesive that needs excellent dielectric properties when making copper-clad laminates. MPI needs a high temperature of more than 300° C. in the imidization of polyamic acid (polyamic acid (polyamic acid)), and there is a problem in processability (for example, patent documentation 3).

[0007] Therefore, in recent years, as the material of having both heat resistance and dielectric properties, maleimide resins such as bismaleimide resins have attracted much attention. Bismaleimide resins are well known for being low-molecular resins, and are high Tg etc., excellent in heat resistance, but poor fluidity when heated, and cured product is hard and brittle. In addition, compared with LCP and MPI, the dielectric properties of bismaleimide resins are insufficient, and under the condition of high temperature and high humidity, relative dielectric constant and dielectric loss tangent increase significantly. Therefore, strongly expect to develop while maintaining heat resistance and moisture resistance, excellent in dielectric properties and low melt viscosity when heated, resin with film forming property.

[0008] In contrast, the use of special maleimide compounds having a dimer diamine skeleton derived from dimer acid as the main resin for the substrate has been disclosed (Patent Documents 4 to 8). Contrary to the properties of general maleimide resins, special maleimide compounds have very excellent dielectric properties, flexibility, and excellent adhesion to adherends such as metals. On the other hand, due to low Tg and high coefficient of thermal expansion (CTE), the dielectric properties change greatly under high temperature environmental conditions, and the heat resistance is not sufficient.

[0009] Prior art literature

[0010] Patent Literature

[0011] [Patent Document 1]: International Publication No. 2019 / 65940

[0012] [Patent Document 2]: Japanese Patent Application Publication No. 2013-74129

[0013] [Patent Document 3]: Japanese Patent Application Publication No. 2019-104818

[0014] [Patent Document 4]: Japanese Patent Application Publication No. 2016-131243

[0015] [Patent Document 5]: Japanese Patent Application Publication No. 2016-131244

[0016] [Patent Document 6]: International Publication No. 2016 / 114287

[0017] [Patent Document 7]: Japanese Patent Application Publication No. 2018-201024

[0018] [Patent Document 8]: Japanese Patent Application Publication No. 2021-25051 Summary of the invention

[0019] Problem that the invention aims to solve

[0020] Therefore, an object of the present invention is to provide a thermosetting maleimide resin composition having a low melt viscosity when heated, excellent flexibility of a cured film as a cured product thereof, low relative dielectric constant and dielectric loss tangent, a high glass transition temperature, a low thermal expansion coefficient, and excellent heat resistance and moisture resistance even when left for a long period of time.

[0021] Solutions to the problem

[0022] The present inventors have conducted intensive studies to solve the above problems and have found that the following thermosetting maleimide composition can achieve the above objects, thereby completing the present invention.

[0023] That is, the present invention relates to the following <1> to <6>.

[0024] <1>

[0025] A thermosetting maleimide resin composition, comprising:

[0026] (A) a bismaleimide compound represented by the following formula (1):

[0027] [Chemical formula 1]

[0028]

[0029] (In formula (1), A independently represents a tetravalent organic group containing a cyclic structure. B independently represents a divalent hydrocarbon group derived from a dimer acid skeleton. Q independently represents a divalent group having a fluorene skeleton or an indene skeleton represented by any one of the following formulas (2-1) or (2-2).

[0030] [Chemical formula 2]

[0031]

[0032] (In formula (2-1), R 1 are independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a (hetero)aryl group having 4 to 10 carbon atoms, a hydroxyl group, an alkoxy group, a halogen group, a trifluoromethyl group, an amino group or a sulfenyl group. In formula (2-2), R 2 are independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a (hetero)aryl group having 4 to 10 carbon atoms, a hydroxyl group, an alkoxy group, a halogen group, a trifluoromethyl group, an amino group or a sulfenyl group.

[0033] W is B or Q. n is 1 to 100, and m is 1 to 100. In addition, the order of each repeating unit enclosed by n and m is not limited, and the bonding method is alternating, block or random.

[0034] (B) a thermosetting resin having one or more maleimide-reactive functional groups selected from the group consisting of alkenyl, maleimide, epoxy, cyanate, hydroxyl, anhydride, (meth)acryloyl and thiol groups, and

[0035] (C) Reaction accelerator.

[0036] <2>

[0037] The thermosetting maleimide resin composition as described in <1>, wherein the content ratio of the component (A) to the component (B) is (A):(B)=95:5 to 50:50 by mass ratio.

[0038] <3>

[0039] The thermosetting maleimide resin composition as described in <1> or <2>, wherein the number average molecular weight of the bismaleimide compound of formula (1) is 3,000 to 50,000.

[0040] <4>

[0041] The thermosetting maleimide resin composition according to any one of <1> to <3>, wherein in the bismaleimide compound of the formula (1), the bonding form of each repeating unit enclosed by n and m is block.

[0042] <5>

[0043] The thermosetting maleimide resin composition as described in any one of <1> to <4>, wherein A in the formula (1) is any one of the tetravalent organic groups represented by the following formulas:

[0044] [Chemical formula 3]

[0045]

[0046] <6>

[0047] The thermosetting maleimide resin composition according to any one of <1> to <5>, wherein the number average molecular weight of the component (B) is 6,000 or less.

[0048] Effects of the Invention

[0049] The thermosetting maleimide resin composition of the present invention has a low melt viscosity when heated. In addition, the cured film as its cured product has excellent flexibility. Further, the thermosetting maleimide resin composition can form a cured product having low relative dielectric constant and dielectric loss tangent at high frequencies, excellent dielectric properties, high glass transition temperature, low thermal expansion coefficient, and excellent heat resistance and moisture resistance.

[0050] Therefore, the thermosetting maleimide resin composition of the present invention can be applied to films attached with uncured resin, cured resin films, prepregs, copper-clad laminates, printed circuit boards, semiconductor packaging materials, adhesives, and metal foils attached with resin. DETAILED DESCRIPTION

[0051] Hereinafter, the present invention will be described in detail.

[0052] The component (A) used in the present invention is a bismaleimide compound represented by the following formula (1).

[0053] [Chemical formula 4]

[0054]

[0055] In formula (1), A independently represents a tetravalent organic group containing a cyclic structure. B independently represents a divalent hydrocarbon group derived from a dimer acid skeleton. Q independently represents a divalent group having a fluorene skeleton or an indene skeleton represented by any one of the following formulas (2-1) or (2-2). In formula (1), W is B or Q. n is 1 to 100, and m is 1 to 100. In addition, the order of each repeating unit enclosed by n and m is not limited, and the bonding method can be alternating, block, or random. The bismaleimide compound of component (A) has a skeleton derived from a dimer acid and a fluorene skeleton or an indene skeleton in the molecule. Therefore, the cured product of the resin composition containing the component (A) can form a cured product with excellent dielectric properties and heat resistance.

[0056] [Chemical formula 5]

[0057]

[0058] In formula (2-1), R 1 Each of them is independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a (hetero)aryl group having 4 to 10 carbon atoms, a hydroxyl group, an alkoxy group, a halogen group, a trifluoromethyl group, an amino group or a sulfenyl group.

[0059] As R in formula (2-1) 1 Examples of the alkyl group having 1 to 5 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl and pentyl.

[0060] As R in formula (2-1) 1 The (hetero)aryl group having 4 to 10 carbon atoms represented by phenyl includes aryl groups having 6 to 10 carbon atoms such as tolyl, xylyl and naphthyl; and heteroaryl groups having 4 to 10 carbon atoms such as furyl, thienyl, pyridyl and indolyl.

[0061] As R in formula (2-1) 1 The alkoxy group represented by alkoxy group includes methoxy group, ethoxy group, n-propoxy group, isopropoxy group, n-butoxy group, isobutoxy group, tert-butoxy group, n-pentyloxy group, isopentyloxy group, hexyloxy group, benzyloxy group, phenethoxy group, allyloxy group, phenoxy group, tolyloxy group, xylyloxy group, naphthyloxy group, furanyloxy group, thienyloxy group, pyridyloxy group and indolyloxy group.

[0062] As R in formula (2-1) 1 Examples of the halogen group represented by include fluoro, chloro, bromo and iodo.

[0063] As R in formula (2-1) 1 , preferably a hydrogen atom. Specific examples of Q having a fluorene skeleton represented by the formula (2-1) include the following structural formulas.

[0064] [Chemical formula 6]

[0065]

[0066] (The atomic bond not bonded to the substituent in the above structural formula is an atomic bond bonded to the nitrogen atom forming the cyclic imide structure in formula (1).)

[0067] As Q having a fluorene skeleton represented by the formula (2-1), a group represented by the following structural formula is particularly preferred.

[0068] [Chemical formula 7]

[0069]

[0070] In formula (2-2), R 2 Each of them is independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a (hetero)aryl group having 4 to 10 carbon atoms, a hydroxyl group, an alkoxy group, a halogen group, a trifluoromethyl group, an amino group or a sulfenyl group.

[0071] As R in formula (2-2) 2 The alkyl group having 1 to 5 carbon atoms includes methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl and pentyl.

[0072] As R in formula (2-2) 2 The (hetero)aryl group having 4 to 10 carbon atoms represented by phenyl includes aryl groups having 6 to 10 carbon atoms such as tolyl, xylyl and naphthyl; and heteroaryl groups having 4 to 10 carbon atoms such as furyl, thienyl, pyridyl and indolyl.

[0073] As R in formula (2-2) 2The alkoxy group represented by ' includes methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentyloxy, isopentyloxy, hexyloxy, benzyloxy, phenethoxy, allyloxy, phenoxy, tolyloxy, xylyloxy, naphthyloxy, furanyloxy, thienyloxy, pyridyloxy and indolyloxy.

[0074] As R in formula (2-2) 2 Examples of the halogen group represented by include a fluoro group, a chloro group, a bromo group and an iodo group.

[0075] As R in formula (2-2) 2 , preferably a hydrogen atom and an alkyl group having 1 to 5 carbon atoms, and particularly preferably a hydrogen atom and a methyl group. Specific examples of Q having an indene skeleton represented by formula (2-2) include the following structural formulas.

[0076] [Chemical formula 8]

[0077]

[0078] (The atomic bond not bonded to the substituent in the above structural formula is an atomic bond bonded to the nitrogen atom forming the cyclic imide structure in formula (1).)

[0079] The divalent group having an aromatic ring represented by Q is a group derived from a diamine having an aromatic ring in the production method described later. Examples of the diamine having an aromatic ring include 9,9-bis(4-aminophenyl)fluorene (hereinafter, also referred to as FDA), 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-fluorophenyl)fluorene (hereinafter, also referred to as FFDA), 9,9-bis(4-amino-3-chlorophenyl)fluorene, 9,9-bis(4-amino-3-hydroxyphenyl)fluorene, 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene, 1- (4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-indene-5-amine (hereinafter also represented as PIDA), 3-(4-aminophenyl)-2,3-dihydro-3-methyl-1,1-diphenyl-1H-indene-5-amine, 2-(4-aminophenyl)-1-ethyl-2,3-dihydro-3-methyl-1H-indene-5-amine, 1,3,3-tris(4-aminophenyl)-2,3-dihydro-1-methyl-1H-indene-5-amine, etc. These diamines can be used alone or in combination of two or more depending on the purpose and application. From the viewpoint that the resin composition containing the bismaleimide compound represented by formula (1) has excellent dielectric properties, a high glass transition temperature, and a low thermal expansion coefficient, the diamine having an aromatic ring is preferably FDA, FFDA or PIDA.

[0080] In formula (1), A independently represents a tetravalent organic group containing a cyclic structure and is a group derived from a tetracarboxylic dianhydride monomer, which may be a group having a fluorene skeleton or a group not having a fluorene skeleton. Examples of the tetracarboxylic dianhydride monomer include pyromellitic dianhydride, 4,4'-carbonyl diphthalic dianhydride, 4,4'-oxydiphthalic dianhydride, 3,4'-oxydiphthalic dianhydride, 4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(4,4'-isopropyldiphenoxy) diphthalic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride. Acid dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride, dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5- , 5", 6,6"-tetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 4,4'-(acetylene-1,2-diyl) diphthalic acid dianhydride, 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic acid 1,4:2,3-dianhydride, 2,3,6,7-naphthalenetetracarboxylic acid 2,3:6,7-dianhydride, naphthalene-1,4,5,8-tetracarboxylic acid dianhydride, bis(1,3-dioxo-1,3- Dihydroisobenzofuran-5-carboxylic acid) 1,4-phenylene ester, 3,4,9,10-perylenetetracarboxylic acid dianhydride, etc. Depending on the purpose, application, etc., these acid anhydrides can be used alone or in combination of two or more. From the viewpoint of the excellent dielectric properties and excellent solubility in solvents of the bismaleimide compound represented by formula (1), 4,4'-(4,4'-isopropylidene diphenyloxy) diphthalic acid dianhydride is preferred.

[0081] In formula (1), B is independently one or more divalent hydrocarbon groups from the dimer acid skeleton. The dimer acid is a liquid dibasic acid with a carbon number of 36 as the main component, which is generated by dimerizing an unsaturated fatty acid with a carbon number of 18 from natural materials such as vegetable oils and fats. The dimer acid skeleton is not a single skeleton, but has a variety of structures and there are several isomers. Representative dimer acids are classified by the names of straight chain type (a), monocyclic type (b), aromatic ring type (c), and polycyclic type (d).

[0082] In the present specification, the dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxyl group of the dimer acid is substituted with a primary aminomethyl group.

[0083] Specifically, the divalent hydrocarbon group derived from the dimer acid skeleton of B in formula (1) may be a branched divalent hydrocarbon group in which two carboxyl groups are substituted with methylene groups in each of the dimer acids (a) to (d) below, but is not limited thereto.

[0084] Furthermore, from the viewpoint of heat resistance and reliability of the cured product, a structure in which the hydrocarbon group derived from the dimer acid skeleton is hydrogenated to reduce the carbon-carbon double bonds in the hydrocarbon group derived from the dimer acid skeleton is more preferred.

[0085] [Chemical formula 9]

[0086]

[0087] As described above, since the dimer acid skeleton has various structures, in this specification, the divalent hydrocarbon group derived from the dimer acid skeleton may be represented by its average structure as -C 36 H 70 -.

[0088] In the formula (1), W is B or Q. W is determined to be either B or Q depending on the manufacturing method described later.

[0089] In formula (1), n ​​is 1 to 100, preferably 1 to 50, and more preferably 1 to 10. In addition, m is 1 to 100, preferably 1 to 50, and more preferably 1 to 10. If n and m are too small, the cured product becomes brittle and may be easily broken, while if n and m are too large, the fluidity decreases and the moldability may be deteriorated.

[0090] The number average molecular weight (Mn) of the bismaleimide compound as component (A) is not particularly limited, and is preferably 3000 to 50000, more preferably 3500 to 20000, and further preferably 4000 to 10000. If the number average molecular weight (Mn) of the bismaleimide compound is within this range, the viscosity of the thermosetting maleimide resin composition of the present invention will not be too high, thereby having excellent fluidity. Moreover, the cured product of the resin composition has high strength.

[0091] The number average molecular weight (Mn) referred to in this specification refers to the number average molecular weight measured by GPC under the following conditions using polystyrene as a standard substance.

[0092] [GPC measurement conditions]

[0093] Elution solvent: tetrahydrofuran

[0094] Flow rate: 0.35mL / min

[0095] column:

[0096] TSKgel guardcolumn SuperHZ-L(4.6mmI.D.×2cm×1)

[0097] TSKgel SuperH-RC(6.0mmI.D.×15cm×2)

[0098] TSKgel SuperHZ4000(4.6mmI.D.×15cm×1)

[0099] TSKgel SuperHZ3000(4.6mmI.D.×15cm×1)

[0100] TSKgel SuperHZ2000(4.6mmI.D.×15cm×2)

[0101] (Both manufactured by TOSOH CORPORATION)

[0102] Column temperature: 40°C

[0103] Sample injection volume: 10 μL (sample concentration: 0.2 mass%-tetrahydrofuran solution)

[0104] Detector: Differential Refractometer (RI)

[0105] In the bismaleimide compound represented by formula (1) of the present invention, the order of the repeating units enclosed by n and m in formula (1) is not limited, and the bonding pattern may be alternating, block or random, but preferably block.

[0106] The method for producing the bismaleimide compound of the component (A) is not particularly limited, and it can be efficiently produced by, for example, the following two methods.

[0107] Manufacturing method 1

[0108] As a production method, it is a production method of a bismaleimide compound having steps A, B and C, wherein step A is a step of synthesizing an amic acid using an acid anhydride represented by the following formula (3) and a diamine having an aromatic ring represented by the following formula (4) and performing ring-closing dehydration;

[0109] [Chemical formula 10]

[0110]

[0111] (In formula (3), A is the same as that shown in formula (1).

[0112] H2N-Q-NH2(4)

[0113] (In formula (4), Q is the same as that shown in formula (1))

[0114] The step B is a step of synthesizing an amic acid and performing ring-closing dehydration after the step A using the reactant obtained in the step A and a diamine derived from a dimer acid skeleton represented by the following formula (5);

[0115] H2N-B-NH2(5)

[0116] (In formula (5), B is the same as that shown in formula (1).

[0117] The step C is a step of synthesizing maleamic acid using the reactant obtained in the step B and maleic anhydride, and capping the terminal of the molecular chain with a maleimide group by ring-closing dehydration.

[0118] Manufacturing method 2

[0119] Another production method is a method for producing a bismaleimide compound having steps A', B' and C', wherein step A' is a step of synthesizing an amic acid from an acid anhydride represented by the following formula (3) and a diamine derived from a dimer acid skeleton represented by the following formula (5), and performing ring-closing dehydration;

[0120] [Chemical formula 11]

[0121]

[0122] (In formula (3), A is the same as that shown in formula (1).

[0123] H2N-B-NH2(5)

[0124] (In formula (5), B is the same as that shown in formula (1).

[0125] The step B' is a step of synthesizing an amic acid and performing ring-closing dehydration using the reactant obtained in the step A' and a diamine having an aromatic ring represented by the following formula (4) after the step A'.

[0126] H2N-Q-NH2(4)

[0127] (In formula (4), Q is the same as that shown in formula (1).

[0128] The step C' is a step of synthesizing maleamic acid using the reactant obtained in the step B' and maleic anhydride, and capping the molecular chain terminal with a maleimide group by ring-closing dehydration.

[0129] Although the above two manufacturing methods are shown, as a basic process, it goes through step A (or step A') of synthesizing amic acid with tetracarboxylic dianhydride and diamine, and performing closed-loop dehydration; then, after step A (or step A'), a diamine different from the previous step A (or step A') is added to synthesize amic acid, and further a closed-loop dehydration is performed. Step B (or step B'); and after step B (or step B'), maleic anhydride is reacted to synthesize maleamic acid, and finally a closed-loop dehydration is performed to terminate the molecular chain end with a maleimide group Step C (or step C'); thereby, a bismaleimide compound can be obtained. The difference between the above two manufacturing methods is mainly that only the order of the types of diamines added is different.

[0130] In the above two production methods, each step can be roughly divided into two types: a synthesis reaction of amic acid or maleamic acid and a ring-closing dehydration reaction, which will be described in detail below.

[0131] In step A (or step A'), first, amic acid is synthesized by reacting a specific tetracarboxylic dianhydride with a specific diamine. The reaction is usually carried out in an organic solvent (e.g., a nonpolar solvent or a high-boiling-point aprotic polar solvent) at room temperature (25°C) to 100°C.

[0132] Next, the ring-closing dehydration reaction of the amic acid is carried out at 100 to 160° C. while removing the water produced as a by-product of the condensation reaction from the system. In order to promote the ring-closing dehydration reaction, an organic solvent (e.g., a nonpolar solvent, a high-boiling-point aprotic polar solvent, etc.) and an acid catalyst may be added.

[0133] As the organic solvent, toluene, xylene, anisole, biphenyl, naphthalene, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), dimethylacetamide (DMAC) etc. can be cited. They can be used alone or in combination of two or more. Among them, from the viewpoint of solubility, aromatic solvents such as toluene, xylene, anisole, biphenyl and naphthalene are preferred, and toluene, xylene or anisole are particularly preferred.

[0134] Examples of the acid catalyst include sulfuric acid, methanesulfonic acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, etc. These may be used alone or in combination of two or more.

[0135] The amount of the acid catalyst used is preferably 0.1 mol or more and 2.0 mol or less, and more preferably 0.2 mol or more and 1.0 mol or less, based on 1 mol of the diamine as a raw material.

[0136] The molar ratio of tetracarboxylic dianhydride to diamine is preferably tetracarboxylic dianhydride / diamine = 1.01 to 1.99 / 1.0, more preferably tetracarboxylic dianhydride / diamine = 1.01 to 1.80 / 1.0, and still more preferably tetracarboxylic dianhydride / diamine = 1.10 to 1.60 / 1.0. By mixing at this ratio, a copolymer containing imide groups at both ends can be synthesized.

[0137] In step B (or step B'), first, the copolymer containing imide groups at both ends obtained in step A (or step A') is reacted with a specific diamine to synthesize an amic acid. The reaction is usually carried out in an organic solvent (e.g., a nonpolar solvent or a high-boiling-point aprotic polar solvent) at room temperature (25°C) to 100°C.

[0138] Similarly, after the reaction is carried out at 100 to 160° C., the ring-closing dehydration reaction of the amic acid is carried out while removing the water produced as a by-product of the condensation reaction from the system. In order to promote the ring-closing dehydration reaction, an organic solvent (e.g., a nonpolar solvent, a high-boiling-point aprotic polar solvent, etc.) and an acid catalyst may be added.

[0139] As the organic solvent, toluene, xylene, anisole, biphenyl, naphthalene, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), dimethylacetamide (DMAC) etc. can be cited. They can be used alone or in combination of two or more. Among them, from the viewpoint of solubility, aromatic solvents such as toluene, xylene, anisole, biphenyl, naphthalene are preferred, and toluene, xylene or anisole are particularly preferred.

[0140] Examples of the acid catalyst include sulfuric acid, methanesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid, etc. These may be used alone or in combination of two or more.

[0141] The amount of the acid catalyst used is preferably 0.1 mol or more and 2.0 mol or less, and more preferably 0.2 mol or more and 1.0 mol or less, based on 1 mol of the diamine as a raw material.

[0142] The molar ratio of the copolymer containing imide groups at both ends to the diamine is preferably 1.0:0.01 to 1.0, more preferably 1.0:0.1 to 1.0.

[0143] In step C (or step C'), maleamic acid is synthesized by reacting the diamine containing amino groups at both ends obtained in step B (or step B') with maleic anhydride at room temperature (25°C) to 100°C, and finally, by performing closed-loop dehydration at 100 to 160°C while removing the by-produced water from the system, the molecular chain ends are capped with maleimide groups, thereby obtaining a bismaleimide compound as the target product.

[0144] According to such a production method, since the obtained bismaleimide compound has a block copolymer structure, the compatibility of the synthesized resin can be made uniform and the compatibility of the synthesized resin can be improved.

[0145] The molar ratio of the diamine having amino groups at both terminals to maleic anhydride is preferably 1.0:1.6 to 2.5, more preferably 1.0:1.8 to 2.2.

[0146] The solution of the bismaleimide compound obtained by the above-mentioned production method can be used to wash the catalyst by a known method (for example, adding water, alcohol, etc., and stirring, standing, and separating the organic solvent and the aqueous solution).

[0147] The bismaleimide compound obtained by above-mentioned manufacture method can be taken out under varnish state, in addition, by adding poor solvent and by reprecipitation etc., can be used as solid powder to carry out refining, separation.Consider from the viewpoint of manufacturing cost, the bismaleimide compound obtained by manufacture method of the present invention is preferably taken out under varnish state.In this case, can obtain the resin varnish containing bismaleimide compound of the present invention and the organic solvent that uses in its manufacture method.

[0148] Examples of the solvent for the resin varnish include the same organic solvents as those used in the production method, and aromatic solvents such as toluene, xylene, anisole, biphenyl and naphthalene are preferred, and toluene, xylene and anisole are particularly preferred.

[0149] The content of the component (A) is preferably 25 to 95% by mass, more preferably 30 to 90% by mass, in the total amount of the composition of the present invention.

[0150] [(B) Thermosetting resin having a maleimide-reactive functional group]

[0151] The component (B) used in the present invention is a thermosetting resin having a maleimide-reactive functional group. Examples of reactive functional groups that can react with maleimide groups include alkenyl groups such as allyl and vinyl, maleimide groups, epoxy groups, cyanate groups, hydroxyl groups, acid anhydride groups, (meth)acryloyl groups, and thiol groups. However, when the component (B) is a thermosetting resin having a maleimide group, the portion of the maleimide compound corresponding to the component (A) is removed from the component (B).

[0152] From the viewpoint of reactivity, the reactive group of the thermosetting resin as the component (B) is preferably a group selected from an alkenyl group such as an allyl group and a vinyl group, a maleimide group, an epoxy group and a (meth)acryloyl group, and from the viewpoint of dielectric properties, an alkenyl group such as an allyl group and a vinyl group, a maleimide group or a (meth)acryloyl group is more preferable.

[0153] The type of thermosetting resin is not limited, for example, triallyl isocyanurate (TAIC) and other allyl compounds with allyl and isocyanuric acid ring, modified polyphenylene ether resins, maleimide resins, epoxy resins, phenolic resins, melamine resins, silicone resins, cyclic imide resins, urea-formaldehyde resins, thermosetting polyimide resins, thermosetting acrylic resins, epoxy silicone hybrid resins, etc. can be cited. From the viewpoint of dielectric properties, allyl compounds, modified polyphenylene ether resins, maleimide resins are more preferred. In addition, (B) component can be used alone or in combination of more than one as long as it is more than one.

[0154] In the resin composition of the present embodiment, the content ratio of the component (A) to the component (B) is preferably a mass ratio of (A): (B) = 95: 5 to 50: 50, more preferably (A): (B) = 90: 10 to 60: 40. If the content ratio of the component (A) is less than the above content ratio, the flexibility of the cured film may be poor, the relative dielectric constant and the dielectric loss tangent may increase, and the Tg may decrease. On the other hand, if the content ratio of the component (B) is less than the above content ratio, the fluidity of the resin composition may be poor when heated.

[0155] The number average molecular weight of the thermosetting resin of the component (B) is preferably 6000 or less, more preferably 4000 or less, and even more preferably 3000 or less. If the number average molecular weight is larger than the above value, compatibility may be deteriorated and the melt viscosity during heating may be increased.

[0156] [(C) Reaction accelerator]

[0157] The component (C) used in the present invention is a reaction accelerator, which is added to accelerate the crosslinking reaction of the maleimide compound as the component (A) and the reaction between the maleimide group in the component (A) and the maleimide group-reactive functional group in the component (B).

[0158] The component (C) is not particularly limited as long as it is a component that accelerates a crosslinking reaction, and examples thereof include a thermal radical polymerization initiator and a thermal anionic polymerization initiator.

[0159] Examples of the thermal radical polymerization initiator include methyl ethyl ketone peroxide, methyl cyclohexanone peroxide, methyl acetoacetate peroxide, acetylacetone peroxide, 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-hexylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 1,1-bis(tert-butylperoxy)cyclododecane, n-butyl 4,4-bis(tert-butylperoxy)valerate, 2,2-bis(tert-butylperoxy)butane, 1,1-bis(tert-butylperoxy)-2-methylcyclohexane, tert-butyl Hydrogen peroxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, tert-hexyl hydroperoxide, dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, α,α'-bis(tert-butylperoxy)diisopropylbenzene, tert-butylisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, isobutyryl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, cinnamic acid peroxide, m-toluoyl peroxide, benzoyl peroxide, diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate , di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, isopropylbenzene peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 1-cyclohexyl-2-methylethyl peroxyneodecanoate Organic peroxides such as hexyl-1-methylethyl ester, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-isobutyrate, tert-butyl peroxymaleate, tert-butyl peroxydodecanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-bis(peroxybenzoyl)hexane, tert-butyl peroxyacetate, tert-hexyl peroxybenzoate, tert-butyl peroxy-m-toluoylbenzoate, tert-butyl peroxybenzoate, bis(tert-butylperoxy)isophthalate, tert-butyl peroxyallyl monocarbonate, and 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone;2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis[N-(2-methylpropyl)-2-methylpropionamide], 2,2'-azobis[N-(2-methylethyl)-2-methylpropionamide], 2,2'-azobis(N-hexyl-2-methylpropionamide), 2,2'-azobis(N-propyl-2-methylpropionamide), 2,2'-azobis(N-ethyl Azo compounds such as 2-methyl-2-methylpropionamide), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], dimethyl-1,1'-azobis(1-cyclohexanecarboxylate). ;

[0160] Examples of the thermal anionic polymerization initiator include amine compounds such as triethylamine, triethylenediamine, 2-(dimethylaminomethyl)phenol, 1,8-diazabicyclo[5.4.0]undecene-7, tris(dimethylaminomethyl)phenol, and benzyldimethylamine; 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2,4-diamino-6-[2-(2-methyl- imidazole compounds such as [(1-imidazolyl)ethyl]-1,3,5-triazine, 2-phenyl-4-hydroxy-5-methylimidazole, etc.; organic phosphorus compounds such as triphenylphosphine, tributylphosphine, trioctylphosphine, tetrabutylphosphonium hexafluorophosphate, tetrabutyltetraphenylphosphonium borate, tetrabutylphosphonium acetate, tetraphenyltetraphenylphosphonium borate, tetraphenylphosphonium bromide, tetrabutylphosphonium bromide, tetrabutylphosphonium laurate, tetraphenylphosphonium hydrogen phthalate, bis(tetraphenylphosphonium) dihydropyromellitic tetracarboxylate, and bis(tetrabutylphosphonium) dihydropyromellitic tetracarboxylate.

[0161] Wherein, in the case of a group having a carbon-carbon double bond such as a maleimide group, an alkenyl group, or a (meth)acryloyl group in a reaction alone with the (A) component or a reactive group in the (B) component, an organic peroxide as a thermal free radical polymerization initiator is preferred. In addition, in the case of a reactive group in the (B) component being an epoxy group, a hydroxyl group, or an anhydride group, an alkaline compound such as an imidazole compound and an amine compound as a thermal anionic polymerization initiator is preferred. These polymerization initiators can be used alone or in combination of two or more.

[0162] The amount of component (C) is not particularly limited, but is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of component (A). If the amount of component (C) is within this range, the physical properties of the resin composition will not be adversely affected, and the resin composition can be fully cured.

[0163] [Adhesiveness-imparting agent]

[0164] The resin composition of the present invention may contain an adhesion-imparting agent (component (D)) as required in order to impart adhesion or pressure-sensitive adhesiveness (pressure-sensitive adhesiveness). Examples of adhesion-imparting agents include acrylic resins, polyurethane resins, phenolic resins, terpene resins, and silane coupling agents. Among them, acrylic resins and silane coupling agents are preferred in terms of imparting adhesion; and terpene resins are preferred in terms of imparting pressure-sensitive adhesiveness (pressure-sensitive adhesiveness). It should be noted that the adhesion-imparting agent of component (D) may be used alone or in combination of two or more.

[0165] The acrylic resin is not particularly limited, and examples thereof include dodecyl acrylate, stearic acid ester, isostearyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-acryloyloxyethyl phthalate, 2-acryloyloxyethyl phosphate, polyethylene glycol diacrylate, tricyclodecane dimethylol diacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, dioxanediol diacrylate, 9,9-di[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate, lauryl methacrylate, phenoxyethyl methacrylate, phenoxydiethylene glycol methacrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, 2-methacryloyloxyethyl phthalate, 2-methacryloyloxyethyl phosphate, polyethylene glycol dimethacrylate, and tricyclodecane dimethylol dimethacrylate.

[0166] Terpene resins are not particularly limited, and examples thereof include homopolymers of terpenes such as monoterpenes such as α-pinene, β-pinene, dipentene, and limonene, sesquiterpenes such as cedrene and farnesene, and diterpenes such as abietic acid, or aromatic modified terpene resins which are copolymers of aromatic vinyl compounds such as styrene and α-methylstyrene and the above terpenes; terpene phenolic resins which are copolymers of phenols such as phenol, cresol, hydroquinone, naphthol, bisphenol A, and the above terpenes, etc. In addition, hydrogenated terpene resins obtained by hydrogenating these terpene resins may also be used.

[0167] The silane coupling agent is not particularly limited, and examples thereof include n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]-trimethoxysilane, methoxytris(ethyleneoxy)propyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane and the like.

[0168] The amount of the adhesion-imparting agent is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, and still more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the total of the components (A) and (B). Within this range, the mechanical properties of the resin composition are not changed, and the adhesive force or pressure-sensitive adhesive force of the resin composition can be further improved.

[0169] [Flame retardant]

[0170] The resin composition of the present invention may contain a flame retardant (component (E)) as necessary in order to impart flame retardancy.

[0171] There are no particular restrictions on the flame retardant, and examples thereof include phosphorus flame retardants, metal hydrates, halogen flame retardants, and guanidine flame retardants. Examples of the phosphorus flame retardant include red phosphorus, ammonium phosphate such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate, inorganic nitrogen-containing phosphorus compounds such as guanidine phosphate and phosphoric acid amide, phosphoric acid, phosphine oxide, triphenyl phosphate, tricresyl phosphate, tri(xylyl) phosphate, tolylene diphenyl phosphate, tolylene di(2,6-xylyl) phosphate, resorcinol bis(di(xylyl) phosphate), resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di(2,6-xylyl) phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene Phosphazene compounds such as bis(diphenyl phosphate), divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl)phenylphosphonate, phenyl diphenylphosphinate, methyl diphenylphosphinate, bis(2-allylphenoxy)phosphazene, and dimethylphenylphosphazene; melamine phosphate; melamine pyrophosphate; melamine polyphosphate, melam polyphosphate, melem polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Examples of metal hydrates include aluminum hydroxide hydrate and magnesium hydroxide hydrate. As halogen flame retardants, hexabromobenzene, pentabromotoluene, ethylenebis(pentabromophenyl), ethylenebis(tetrabromophthalimide), 1,2-dibromo-4-(1,2-dibromoethyl)cyclohexane, tetrabromocyclooctane, hexabromocyclododecane, bis(tribromophenoxy)ethane, brominated polyphenylene ether, brominated polystyrene, 2,4,6-tris(tribromophenoxy)-1,3,5-triazine, etc. can be cited. As guanidine flame retardants, guanidine sulfonate, guanidine phosphate, etc. can be cited. It should be noted that the flame retardant of component (E) can be used alone or in combination of two or more.

[0172] The amount of the flame retardant is not particularly limited, but is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 50 parts by mass, and further preferably 1 to 30 parts by mass relative to 100 parts by mass of the total of the components (A) and (B). If the amount of the flame retardant is within this range, the mechanical properties of the resin composition will not be changed, and flame retardancy can be imparted to the resin composition.

[0173] [Inorganic filler]

[0174] The resin composition of the present invention may further contain an inorganic filler (component (F)).

[0175] There are no particular restrictions on the inorganic filler, and examples thereof include metal oxides such as silicon dioxide, titanium dioxide, yttrium oxide, aluminum oxide, magnesium oxide, zinc oxide, and beryllium oxide; metal nitrides such as boron nitride, aluminum nitride, and silicon nitride; carbonaceous particles such as silicon carbide, diamond, and graphene; hollow particles such as hollow silica spheres (hollow silica), hollow carbon spheres, hollow alumina spheres, and hollow aluminosilicate spheres; metal monomers such as gold, silver, copper, palladium, aluminum, nickel, iron, cobalt, titanium, manganese, zinc, tungsten, platinum, lead, and tin; alloys such as solder and steel; stainless steel, Fe-Cr-Al-Si alloy, Fe-S Magnetic metal alloys such as i-Al alloy, Fe-Ni alloy, Fe-Cu-Si alloy, Fe-Si alloy, Fe-Si-B (-Cu-Nb) alloy, Fe-Si-Cr-Ni alloy, Fe-Si-Cr alloy, Fe-Si-Al-Ni-Cr alloy; ferrites such as hematite (Fe2O3), magnetite (Fe3O4), Mn-Zn ferrite, Ni-Zn ferrite, Mg-Mn ferrite, Zr-Mn ferrite, Ti-Mn ferrite, Mn-Zn-Cu ferrite, barium ferrite, strontium ferrite. These may be used alone or in combination of two or more.

[0176] By adding metal oxides, metal nitrides, and carbon-containing particles, the linear expansion coefficient of the cured resin composition can be reduced and the thermal conductivity can be improved; by adding hollow particles, the relative dielectric constant, dielectric loss tangent, density, etc. of the cured resin composition can be reduced; by adding metals and alloys, the electrical conductivity and thermal conductivity of the cured resin composition can be improved; by adding ferrites, the cured resin composition can be given electromagnetic wave absorption properties.

[0177] There are no particular restrictions on the shape of the inorganic filler, and examples thereof include spherical, flaky, thin-flaked, needle-shaped, rod-shaped, and elliptical shapes. Among them, spherical, flaky, thin-flaked, elliptical, and rod-shaped are preferred, and spherical, flaky, thin-flaked, and elliptical shapes are more preferred.

[0178] There is no particular limitation on the primary particle size of the inorganic filler, but the median particle size measured by a laser diffraction particle size distribution measuring device is preferably 0.05 to 500 μm, preferably 0.1 to 300 μm, and more preferably 1 to 100 μm. If the primary particle size of the inorganic filler is within this range, it is easy to evenly disperse the inorganic filler in the resin composition, and the inorganic filler will not precipitate, separate, or become uneven over time, so it is preferred.

[0179] The amount of the inorganic filler is not particularly limited, but is preferably 10 to 500 parts by mass, more preferably 30 to 400 parts by mass, and further preferably 50 to 300 parts by mass relative to 100 parts by mass of the total of the components (A) and (B) in the composition of the present invention. If the amount of the inorganic filler is within this range, the effect of the inorganic filler can be fully exerted while maintaining the strength of the resin composition.

[0180] (Other additives)

[0181] In the range that does not impair the effect of the present invention, various additives may be added to the thermosetting maleimide resin composition of the present invention as required. As such additives, organopolysiloxanes having reactive functional groups, non-functional silicone oils, thermoplastic resins, thermoplastic elastomers, organic synthetic rubbers, photosensitizers, light stabilizers, polymerization inhibitors, pigments, dyes, etc. may be cited. In addition, in order to improve the electrical properties of the cured product of the thermosetting maleimide resin composition, ion trapping agents, etc. may also be added as other additives.

[0182] [Production method]

[0183] The method for producing the resin composition of the present invention may include adding component (A), component (B) and component (C) and, if necessary, other additives, and mixing them using, for example, a planetary mixer, a stirrer, a ball mill, a bead mill, a roll mill or the like.

[0184] The thermosetting maleimide resin composition of the present invention can be dissolved in an organic solvent and treated as a varnish. The thermosetting maleimide resin composition is formed into a varnish, so that it is easy to be formed into a sheet or film; in addition, it is also easy to apply and impregnate to glass cloth made of E glass, low dielectric glass, quartz glass, etc. As long as it is an organic solvent that can dissolve the thermosetting resin components of (A) component and (B) component, it can be used without restriction. As an organic solvent, for example, toluene, xylene, anisole, methyl ethyl ketone (MEK), cyclohexanone, cyclopentanone, etc. can be preferably used. The above-mentioned organic solvents can be used alone or in combination of two or more. The concentration of the thermosetting maleimide resin composition of the present invention in the varnish is preferably 5 to 80% by mass, more preferably 10 to 75% by mass.

[0185] The thermosetting maleimide resin composition of the present invention can be formed into an uncured resin sheet or an uncured resin film by applying the above-mentioned varnish to a substrate and removing the solvent, or can be formed into a cured resin sheet or a cured resin film by further curing it. In addition, it can be used as a prepreg, a substrate material, an adhesive, a semiconductor packaging material, or a metal foil with a resin attached. It can be used without restriction in terms of the method and mode of use. The use examples are illustrated as follows, but are not limited thereto.

[0186] For example, after a thermosetting maleimide resin composition dissolved in an organic solvent is applied to a substrate, it is usually heated at a temperature of 80°C or more, preferably at a temperature of 100°C or more, for 0.5 to 5 hours to remove the organic solvent, and further, heated at a temperature of 130°C or more, preferably at a temperature of 150°C or more, for 0.5 to 10 hours to form a maleimide resin cured film having a flat surface and being strong. The temperatures in the drying process for removing the organic solvent and the subsequent heating and curing process can be respectively constant, but it is preferred to increase the temperature in stages. Thus, while removing the organic solvent from the composition, the curing reaction of the resin can be effectively promoted. As a coating method, a method using a spin coater, a slit coater, a spray coater, a dip coater, and a rod coater can be cited, but there is no particular limitation.

[0187] As the substrate, a commonly used substrate can be used, for example, polyolefin resins such as polyethylene (PE) resin, polypropylene (PP) resin, polystyrene (PS) resin; polyester resins such as polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polycarbonate (PC) resin, etc., and the surfaces of these substrates can also be subjected to demolding treatment. In addition, although there is no particular limitation on the thickness of the coating, the thickness of the coating after distilling off the solvent is in the range of 1 to 100 μm, preferably in the range of 3 to 80 μm. Furthermore, a covering film can also be used on the coating.

[0188] Alternatively, each component may be preliminarily mixed and the mixture may be extruded into a sheet or film using a melt kneader to produce an uncured resin film (uncured resin sheet) or a cured resin film (cured resin sheet).

[0189] [Prepreg]

[0190] The prepreg related to one embodiment of the present invention comprises the thermosetting maleimide resin composition of the present invention and a fiber substrate. The thermosetting maleimide resin composition in the prepreg can also be a semi-cured product of the resin composition. It should be noted that the semi-cured product refers to a state in which the resin composition is cured to a degree that it can be further cured. That is, the semi-cured product is a state in which the resin composition is semi-cured, i.e., a so-called B-stage state. On the other hand, the uncured state is sometimes referred to as the A-stage.

[0191] The fiber substrate may be E glass, low dielectric glass, quartz glass, and further may be S glass, T glass, etc. The type of glass used is not particularly limited, but from the viewpoint of exerting the characteristics of the thermosetting maleimide resin composition of the present invention, quartz glass cloth having low relative dielectric constant and dielectric loss tangent is preferred.

[0192] The thickness of the fiber substrate is not limited, but is preferably 5 to 500 μm, more preferably 10 to 100 μm, and even more preferably 20 to 80 μm. Within this range, a prepreg having excellent flexibility, low warpage, and high strength can be obtained.

[0193] In order to improve the dielectric properties and increase the affinity with the resin, these fiber base materials may be surface treated by heating or using a silane coupling agent or the like.

[0194] When manufacturing the prepreg, the thermosetting maleimide resin composition is preferably formed into a varnish-like resin varnish in order to be impregnated into a fiber substrate as a substrate for forming the prepreg. Such a varnish-like resin composition (resin varnish) is prepared, for example, as follows.

[0195] First, each component that can be dissolved in the organic solvent in the composition of the resin combination is added to the organic solvent and dissolved. At this point, it is also possible to heat as required. Then, add the components that are insoluble in the organic solvent such as the inorganic filler used as required, use a ball mill, a bead mill, a planetary mixer, a roller mill etc., so that it is dispersed into a given dispersion state, thus preparing a varnish-like resin combination (resin varnish). As the organic solvent used here, as long as it is a solvent that does not hinder the curing reaction, there is no particular limitation. Specifically, for example, toluene, xylene, anisole, methyl ethyl ketone (MEK), cyclohexanone and cyclopentanone etc. can be exemplified.

[0196] Next, after impregnating the varnish-like resin composition (resin varnish) into the fiber base material by a method such as impregnation or coating, it is dried. If necessary, the impregnation may be repeated for a plurality of times. In addition, at this time, by repeatedly impregnating with a plurality of resin compositions having different compositions and concentrations, the desired composition and impregnation amount may be finally adjusted.

[0197] The fiber substrate impregnated with the thermosetting maleimide resin composition (resin varnish) is heated under desired heating conditions, for example, at 80° C. to 200° C. for 1 minute to 2 hours. By heating, a prepreg containing the thermosetting maleimide resin composition before curing (A stage) or in a semi-cured state (B stage) can be obtained.

[0198] The content of the resin composition in the prepreg is not particularly limited, but is preferably 20 to 90% by volume, more preferably 30 to 80% by volume, and still more preferably 40 to 70% by volume. Within this range, the bonding strength to the conductor can be improved while maintaining dielectric properties and low warpage.

[0199] The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 25 to 300 μm, and even more preferably 40 to 200 μm. Within this range, a copper-clad laminate can be produced satisfactorily.

[0200] [Copper Clad Laminate]

[0201] The copper foil and the prepreg of the present invention are stacked and pressed, and then heated and cured to be used as a copper-clad laminate.

[0202] There is no particular limitation on the method for producing the copper-clad laminate. For example, the copper-clad laminate can be produced by using 1 to 20 sheets, preferably 2 to 10 sheets, of the prepreg, placing copper foil on one or both sides of the prepreg, laminating the prepreg, and heat-curing the prepreg.

[0203] The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and still more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate can be formed while maintaining high reliability.

[0204] There is no particular restriction on the molding conditions of the copper-clad laminate. For example, a multistage press, a multistage vacuum press, a continuous molding, an autoclave molding machine, etc. can be used to mold the copper-clad laminate at a temperature of 100 to 400° C., a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. In addition, the prepreg, copper foil, and inner layer circuit board of the present invention can be combined for molding to form a copper-clad laminate.

[0205] [Printed Circuit Board]

[0206] The copper-clad laminate of the present invention can also be used as a printed circuit board by circuit processing. The circuit processing method is not particularly limited, and examples thereof include hole forming processing, metal plating processing, and circuit forming processing by etching of metal foil.

[0207] Alternatively, a printed wiring board may be produced by a build-up process in which the resin composition or prepreg of the present invention and copper foil are sequentially laminated.

[0208] [Semiconductor packaging materials]

[0209] The thermosetting maleimide resin composition of the present invention can also be used as a semiconductor packaging material.

[0210] There are no particular restrictions on the method for producing semiconductor packaging materials. For example, the method may be a method in which component (A) and component (B) and other components as required are matched at a given composition ratio, mixed sufficiently and uniformly by a stirrer, etc., melt-mixed by a hot roller, a kneader, an extruder, etc., cooled and solidified, and then crushed into a suitable size for production. The obtained resin composition can be used as a packaging material.

[0211] As a general molding method using semiconductor packaging materials, transfer molding and compression molding can be mentioned. In the transfer molding method, a transfer molding machine is used to mold the semiconductor packaging materials at a molding pressure of 5 to 20 N / mm. 2 , the molding temperature is 120-190°C, the molding time is 30-500 seconds, preferably the molding temperature is 150-185°C, the molding time is 30-180 seconds. In addition, in the compression molding method, a compression molding machine is used, and the molding temperature is 120-190°C, the molding time is 30-600 seconds, preferably the molding temperature is 130-160°C, and the molding time is 120-300 seconds. Moreover, in the above molding methods, post-curing can be performed at 150-225°C for 0.5 to 20 hours.

[0212] [Adhesive]

[0213] The thermosetting maleimide resin composition of the present invention can also be used as an adhesive.

[0214] There is no particular limitation on the method for producing the adhesive, and the method may be, for example, a method in which component (A) and component (B) and other components added as needed are matched at a given composition ratio, mixed using a mixer such as a planetary mixer, and then kneaded and mixed using a three-roll mill to improve dispersibility as needed. The resulting resin composition may be used as an adhesive.

[0215] As the method of using the adhesive, any conventionally known method and apparatus may be used. Typical curing conditions are a temperature in the range of 100 to 200°C, preferably in the range of 120 to 180°C, and a time in the range of 1 to 8 hours, preferably in the range of 1.5 to 3 hours.

[0216] [Resin-coated metal foil]

[0217] The thermosetting maleimide resin composition of the present invention can also be used as a resin-attached metal foil.

[0218] The method for producing the resin-attached metal foil is not particularly limited, and for example, the varnish-like resin composition is prepared, the varnish is applied to a supporting substrate using a die coater, the organic solvent is dried by heating or spraying hot air, and the semi-cured, and the metal foil is then attached to an uncured resin film. The obtained film can be used as the resin-attached metal foil.

[0219] The drying conditions are not particularly limited. The content of the organic solvent in the resin composition layer is dried to 10% by mass or less, preferably to 5% by mass or less. The drying conditions vary depending on the amount of organic solvent in the varnish and the boiling point of the organic solvent. For example, in the case of a varnish containing 30 to 60% by mass of an organic solvent, a resin composition layer can be formed by drying at 50 to 150° C. for about 3 to 10 minutes. It should be noted that if drying is performed for a long time at a higher temperature, the composition may undergo a curing reaction, thereby causing the composition to solidify.

[0220] The metal foil to be attached is not particularly limited, and examples thereof include copper foil and aluminum foil.

[0221] In addition, a protective film based on the support body can be further laminated on the surface that does not contact the support body. By laminating the protective film, garbage and the like can be prevented from adhering to the surface of the metal foil or causing damage to the surface of the metal foil. The metal foil with the resin attached can be rolled into a tube for storage.

[0222] [Example]

[0223] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. In the Examples and Comparative Examples, "room temperature" means 25°C.

[0224] The molecular weights shown in the following examples refer to the number average molecular weight (Mn) measured by gel permeation chromatography (GPC) using polystyrene as a standard substance. The measurement conditions are shown below.

[0225] [GPC Measurement Conditions]

[0226] Elution solvent: Tetrahydrofuran

[0227] Flow rate: 0.35 mL / min

[0228] Column:

[0229] TSKgel guardcolumn SuperHZ-L (4.6 mm I.D. × 2 cm × 1)

[0230] TSKgel SuperH-RC (6.0 mm I.D. × 15 cm × 2)

[0231] TSKgel SuperHZ4000 (4.6 mm I.D. × 15 cm × 1)

[0232] TSKgel SuperHZ3000 (4.6 mm I.D. × 15 cm × 1)

[0233] TSKgel SuperHZ2000 (4.6 mm I.D. × 15 cm × 2)

[0234] (All manufactured by TOSOH CORPORATION)

[0235] Column temperature: 40 °C

[0236] Sample injection volume: 10 μL (Sample concentration: 0.2 mass%-tetrahydrofuran solution)

[0237] Detector: Differential refractometer (RI)

[0238] <Component A: Bismaleimide compound>

[0239] [Synthesis Example 1] Synthesis of Bismaleimide Compound A-1

[0240] 52.27g (0.150 mol) of 9,9-bis(4-aminophenyl)fluorene (hereinafter also referred to as FDA), 104.10g (0.200 mol) of 4,4'-(4,4'-isopropyldiphenyloxy)diphthalic anhydride, 250g of toluene, 250g of N-methyl-2-pyrrolidone and 9.61g (0.100 mol) of methanesulfonic acid were added to a 1L glass four-necked flask with a stirrer, a Dean-Stark tube, a cooling condenser and a thermometer, and the mixture was stirred at 80°C for 3 hours to synthesize amic acid. Then, the mixture was directly heated to 120°C and stirred for 8 hours while distilling off the by-product water to synthesize a block copolymer. Then, 53.44g (0.100 mol) of Priamine-1075 (manufactured by CRODA, with an average composition formula of H2N-C 36 H 70 -NH2) was added to a flask containing a block copolymer solution cooled to 80°C, and stirred at 80°C for 2 hours to synthesize amic acid. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-produced water, thereby synthesizing a two-terminal diamine. After the flask containing the obtained two-terminal diamine solution was cooled to room temperature, 10.79g (0.110 mol) of maleic anhydride was added, and maleamic acid was synthesized by stirring at room temperature for 2 hours. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-produced water, thereby synthesizing bismaleimide. The obtained solution was washed 10 times with a mixed aqueous solution of water and isopropanol to remove impurities such as catalysts. Then, water in the system was azeotropically dehydrated with toluene by reduced pressure distillation to obtain a brown varnish solution having a solid content of 50% by mass of bismaleimide having a structure represented by the following formula (A-1) dissolved in toluene. The number average molecular weight of the obtained bismaleimide compound was 6,200.

[0241] [Chemical formula 12]

[0242]

[0243] m≈3, n≈4 (both are average values)

[0244] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid backbone derived from a dimer diamine (Priamine-1075).

[0245] [Synthesis Example 2] Synthesis of Bismaleimide Compound A-2

[0246] 64.07g (0.167 mol) of 9,9-bis (4-amino-3-fluorophenyl) fluorene, 104.10g (0.20 mol) of 4,4'- (4,4'-isopropyldiphenyloxy) diphthalic anhydride, 250g of toluene, 250g of N-methyl-2-pyrrolidone and 9.61g (0.10 mol) of methanesulfonic acid were added to a 1L glass four-necked flask with a stirrer, a Dean-Stark tube, a cooling condenser and a thermometer, and the mixture was stirred at 80°C for 3 hours to synthesize amic acid. Then, the mixture was directly heated to 120°C and stirred for 8 hours while distilling off the by-product water to synthesize a block copolymer. Then, 44.53g (0.083 mol) of Priamine-1075 (manufactured by CRODA, with an average composition formula of H2N-C 36 H 70 -NH2) was added to a flask containing a block copolymer solution cooled to 80°C, and stirred at 80°C for 2 hours to synthesize amide acid. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-produced water, thereby synthesizing a two-terminal diamine. After the flask containing the obtained two-terminal diamine solution was cooled to room temperature, 10.79g (0.110 mol) of maleic anhydride was added, and maleamic acid was synthesized by stirring at room temperature for 2 hours. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-produced water, thereby synthesizing bismaleimide. The obtained solution was washed 10 times with a mixed aqueous solution of water and isopropanol to remove impurities such as catalysts. Then, water in the system was azeotropically dehydrated with toluene by vacuum distillation to obtain a brown varnish solution having a solid content of 50% by mass of bismaleimide having a structure represented by the following formula (A-2) dissolved in toluene. The number average molecular weight of the obtained bismaleimide compound was 6,800.

[0247] [Chemical formula 13]

[0248]

[0249] m≈2, n≈4 (both are average values)

[0250] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid backbone derived from a dimer diamine (Priamine-1075).

[0251] [Synthesis Example 3] Synthesis of Bismaleimide Compound A-3

[0252] In addition to using 44.40 g (0.167 mol) of 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-inden-5-amine, 9,9-bis(4-amino-3-fluorophenyl)fluorene, 104.10 g (0.200 mol) of 4,4'-(4,4'-isopropylidene diphenyloxy) diphthalic anhydride, 250 g of toluene, 250 g of N-methyl-2-pyrrolidone and 9.61 g (0.10 mol) of methanesulfonic acid, a 1L glass four-necked flask equipped with a stirrer, a Dean-Stark tube, a cooling condenser and a thermometer was added, and the mixture was stirred at 80° C. for 3 hours to synthesize amic acid. Then, the mixture was heated to 120° C. and stirred for 8 hours while distilling off the by-produced water to synthesize a block copolymer. Then, 44.53 g (0.083 mol) of Priamine-1075 (manufactured by CRODA, with an average composition formula of H2N-C 36 H 70 -NH2) was added to a flask containing a block copolymer solution cooled to 80°C, and stirred at 80°C for 2 hours to synthesize amide acid. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-produced water, thereby synthesizing a two-terminal diamine. After the flask containing the obtained two-terminal diamine solution was cooled to room temperature, 10.79g (0.110 mol) of maleic anhydride was added, and maleamic acid was synthesized by stirring at room temperature for 2 hours. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-produced water, thereby synthesizing bismaleimide. The obtained solution was washed 10 times with a mixed aqueous solution of water and isopropanol to remove impurities such as catalysts. Then, water in the system was azeotropically dehydrated with toluene by vacuum distillation to obtain a brown varnish solution having a solid content of 50% by mass in which a bismaleimide compound having a structure represented by the following formula (A-3) was dissolved in toluene. The number average molecular weight of the obtained bismaleimide compound was 7,700.

[0253] [Chemical formula 14]

[0254]

[0255] m≈3, n≈6 (both are average values)

[0256] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid backbone derived from a dimer diamine (Priamine-1075).

[0257] [Synthesis Example 4] Synthesis of Bismaleimide Compound A'-1

[0258] 29.71g (0.167 mol) of 2,5-diethyl-4-methylbenzene-1,3-diamine and 104.10g (0.20 mol) of 4,4'-(4,4'-isopropyldiphenyloxy) diphthalic anhydride, 250g of toluene, 250g of N-methyl-2-pyrrolidone and 9.61g (0.10 mol) of methanesulfonic acid were placed in a 1L glass four-necked flask with a stirrer, a Dean-Stark tube, a cooling condenser and a thermometer, and stirred at 80°C for 3 hours to synthesize amic acid. Then, it was directly heated to 120°C and stirred for 8 hours while distilling off the by-product water to synthesize a block copolymer. Then, 44.53g (0.083 mol) of Priamine-1075 (manufactured by CRODA, with an average composition formula of H2N-C 36 H 70 -NH2 represented by a dimer diamine) was added to a flask containing a block copolymer solution cooled to 80°C, and stirred at 80°C for 2 hours to synthesize amic acid. Then, it was directly heated to 120°C and stirred for 8 hours while distilling out the by-produced water, thereby synthesizing a two-terminal diamine. After the flask containing the obtained two-terminal diamine solution was cooled to room temperature, 10.79g (0.110 mol) of maleic anhydride was added, and maleamic acid was synthesized by stirring at room temperature for 2 hours. Then, it was directly heated to 120°C and stirred for 8 hours while distilling out the by-produced water, thereby synthesizing bismaleimide. The obtained solution was washed 10 times with a mixed aqueous solution of water and isopropanol to remove impurities such as catalysts. Then, water in the system was azeotropically dehydrated with toluene by reduced pressure distillation to obtain a brown varnish solution having a solid content of 50% by mass in which a bismaleimide compound having a structure represented by the following formula (A'-1) was dissolved in toluene. The number average molecular weight of the obtained bismaleimide compound was 5,900.

[0259] [Chemical formula 15]

[0260]

[0261] m≈2, n≈3 (both are average values)

[0262] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid backbone derived from a dimer diamine (Priamine-1075).

[0263] (A'-2): A bismaleimide compound represented by the following formula (A'-2) (BMI-2500, number average molecular weight: 4500, manufactured by Designer Molercules Inc.)

[0264] [Chemical Formula 16]

[0265]

[0266] m ≈ 3, n ≈ 5 (both are average values)

[0267] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid skeleton of a dimer diamine (Priamine - 1075).

[0268] (A’ - 3): A bismaleimide compound (BMI - 2300, number average molecular weight: 400, manufactured by Daiwa Kasei Kogyo Co., Ltd., Japan) represented by the following formula (A’ - 3)

[0269] [Chemical Formula 17]

[0270]

[0271] n ≈ 2 (average value)

[0272] <Component B: Thermosetting resin>

[0273] (B - 1): A compound having one isocyanurate ring and three allyl groups in one molecule (TAIC, number average molecular weight: 200, manufactured by Mitsubishi Chemical Corporation, Japan)

[0274] (B - 2): A compound having one isocyanurate ring and two allyl groups in one molecule (L - DAIC, number average molecular weight: 400, manufactured by Shikoku Kasei Kogyo Co., Ltd., Japan)

[0275] (B - 3): A bismaleimide compound containing a dimer acid skeleton (SLK - 6895, number average molecular weight: 1000, manufactured by Shin - Etsu Chemical Co., Ltd., Japan)

[0276] (B - 4) Terminal methacryloyl - modified polyphenylene ether resin (SA9000, number average molecular weight: 2000, manufactured by SABIC)

[0277] <Component C: Reaction promoter>

[0278] (C - 1): 2,5 - Dimethyl - 2,5 - bis(tert - butylperoxy)hexane (Trigonox 101, manufactured by Japan Kayaku Nouryon Co., Ltd.)

[0279] <Other components>

[0280] (D) Adhesion - imparting agent

[0281] (D-1): 3-(Methacryloyloxy)propyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0282] (E) Flame retardant

[0283] (E-1): Resorcinol bis(di(xylyl) phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.)

[0284] (F) Inorganic filler

[0285] (F-1): Toluene slurry of spherical silica having an average particle size of 0.5 μm (5SV-CT1, manufactured by Admatechs Corporation, solid content concentration 75% by mass)

[0286] <Preparation of resin varnish>

[0287] Regarding Examples 1 to 11 and Comparative Examples 1 to 6, the ratios (parts by mass) shown in Tables 1 and 2 were supplemented, i.e., 100 parts by mass of anisole was added to a total of 100 parts by mass of each component. The components were put into a 500 mL four-necked flask with a serpentine cooling tube and a stirring device, stirred at 80° C. for 30 minutes, and then cooled to room temperature to obtain a varnish-like resin composition (resin varnish).

[0288] <Preparation of Uncured Resin Film>

[0289] The resin varnish obtained in the above steps was applied on a support film composed of a PET film having a thickness of 38 μm using a roll coater and dried at 120° C. for 10 minutes to remove the solvent, thereby forming an uncured resin film having a thickness of 80 μm on the support film.

[0290] <Minimum Melt Viscosity>

[0291] After peeling the uncured resin film from the support film, a 1 mm thick test piece was prepared by compressing the uncured resin film while heating it to 100°C. Using the test piece, the minimum melt viscosity (Pa·s) was measured by a parallel plate viscoelasticity measuring device ("Soliquid Meter MR-300" manufactured by Rheology). The measurement conditions were a starting temperature in the temperature range of 120°C to 180°C, a heating rate of 10°C / min, a measurement temperature interval of 2°C, and a vibration frequency of 2Hz. The lowest value of the continuous viscosity measurement was taken as the measured value of the minimum melt viscosity, and was evaluated based on the following standards. The evaluation results are shown in Tables 1 and 2.

[0292] (○) The minimum melt viscosity is less than 1200 Pa·s

[0293] (×) Minimum melt viscosity is 1200 Pa·s or more

[0294] <Preparation of Cured Resin Film>

[0295] The uncured resin film obtained in the above steps was heated under the conditions of 180° C. for 2 hours in a nitrogen atmosphere to obtain a cured resin film.

[0296] <Flexibility of Cured Resin Film>

[0297] The cured resin film was folded 180 degrees five times, and the cured resin film having no defects such as cracks was evaluated as ○, and the cured resin film having defects such as cracks was evaluated as ×. The evaluation results are shown in Tables 1 and 2.

[0298] <Relative dielectric constant, dielectric loss tangent>

[0299] A network analyzer (E5063-2D5 manufactured by Keysight Technologies, Inc.) and a dielectric strip line (manufactured by KEYCOM Corporation.) were connected, and the cured resin film was dried at 120°C for 1 hour, and stored in a room at 25°C and 50% humidity for 24 hours, and the relative dielectric constant and dielectric loss tangent of the cured resin film at a frequency of 10 GHz were measured. The evaluation results are shown in Tables 1 and 2.

[0300] <Humidity resistance test>

[0301] To confirm moisture resistance, the cured resin film was left to stand at 85°C and 85% humidity for 1000 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured in the same manner as above.

[0302] <Heat resistance test>

[0303] In order to confirm the high temperature heat resistance, the cured resin film was left to stand at 150° C. in an air atmosphere for 1000 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured in the same manner as above. The evaluation results are shown in Tables 1 and 2.

[0304] <Glass transition temperature (Tg)>

[0305] The storage modulus (MPa) of the cured resin film was measured by DMA Q800 (manufactured by TAinstruments.com) in the range of -20°C to 300°C, and the peak temperature obtained by plotting the value of Tanδ derived from the obtained storage modulus and loss modulus values ​​was taken as the glass transition temperature (Tg). The measurement conditions were a sample of 40 mm in length × 5 mm in width × 80 μm in thickness, a heating rate of 5°C / min, a frequency of 10 Hz, a tensile mode, and an amplitude of 15 μm. The evaluation results are shown in Tables 1 and 2.

[0306] <Coefficient of Thermal Expansion>

[0307] The thermal expansion coefficient (CTE) of the cured resin film was measured in the range of -50°C to 300°C by TMA Q400 (manufactured by TAinstruments.com), and the thermal expansion coefficient in the range of 0°C to 40°C was calculated. The measurement conditions were a sample of 30 mm in length × 3 mm in width × 80 μm in thickness, a heating rate of 5°C / min, and a test load of 0.075 N. The evaluation results are shown in Tables 1 and 2.

[0308] [Table 1]

[0309]

[0310] [Table 2]

[0311]

[0312] It can be seen from the above evaluation results that the thermosetting maleimide resin composition of the present invention has a low minimum melt viscosity, the cured resin film of the thermosetting bismaleimide resin composition has good flexibility, low relative dielectric constant and dielectric loss tangent, excellent moisture resistance and heat resistance, high glass transition temperature, and low thermal expansion coefficient.

[0313] It can also be seen from the above evaluation results that, in particular, compared with the thermosetting maleimide resin composition of Comparative Example 1 having the same resin skeleton except that the divalent group having an aromatic ring in the component (A) contained in the thermosetting maleimide resin composition of the present invention is replaced by a divalent group not having a fluorene skeleton or an indene skeleton, the thermosetting maleimide resin composition of the present invention has a lower minimum melt viscosity, and the relative dielectric constant and dielectric loss tangent of the cured resin film of the thermosetting maleimide resin composition are low, and the change in its dielectric properties is small even in a high temperature environment, and it is excellent in heat resistance.

[0314] [Industrial Applicability]

[0315] If it is a thermosetting maleimide composition of the present invention, a thermosetting maleimide resin composition can be provided, and its minimum melt viscosity is low. Since the cured product of the thermosetting maleimide resin composition has a low thermal expansion coefficient, a high glass transition temperature (Tg), excellent moisture resistance and heat resistance, even under a high temperature environment, it is possible to impart a cured product with a low relative dielectric constant, a low dielectric loss tangent, and high reliability. The thermosetting maleimide composition of the present invention, specifically, can be used for prepregs, copper-clad laminates, printed circuit boards, semiconductor packaging materials, adhesives, and metal foils attached with resins for electronic devices facing high-frequency bands that require insulating materials with excellent dielectric properties as a prerequisite.

Claims

1. A thermosetting maleimide resin composition, comprising: (A) a bismaleimide compound represented by the following formula (1): [Chemical formula 1] In formula (1), A independently represents a tetravalent organic group containing a cyclic structure, B independently represents a divalent hydrocarbon group derived from a dimer acid skeleton, Q independently represents a divalent group having a fluorene skeleton or an indene skeleton represented by any one of the following formulas (2-1) or (2-2), [Chemical formula 2] In formula (2-1), R 1 are independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an aryl group or a heteroaryl group having 4 to 10 carbon atoms, a hydroxyl group, an alkoxy group, a halogen group, a trifluoromethyl group, an amino group or a sulfenyl group. In formula (2-2), R 2 are independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an aryl group or a heteroaryl group having 4 to 10 carbon atoms, a hydroxyl group, an alkoxy group, a halogen group, a trifluoromethyl group, an amino group or a sulfenyl group, W is B or Q, n is 1 to 100, and m is 1 to 100. In addition, the order of each repeating unit enclosed by n and m is not limited, and the bonding method is alternating, block or random. (B) a thermosetting resin having one or more maleimide-reactive functional groups selected from the group consisting of alkenyl, maleimide, epoxy, cyanate, hydroxyl, anhydride, (meth)acryloyl and thiol groups, and (C) Reaction accelerator.

2. The thermosetting maleimide resin composition according to claim 1, wherein The content ratio of the component (A) to the component (B) is (A):(B)=95:5 to 50:50 by mass ratio.

3. The thermosetting maleimide resin composition according to claim 1, wherein The number average molecular weight of the bismaleimide compound of formula (1) is 3,000 to 50,000.

4. The thermosetting maleimide resin composition according to claim 1, wherein In the bismaleimide compound of the formula (1), the bonding form of each repeating unit enclosed by n and m is block.

5. The thermosetting maleimide resin composition according to claim 1, wherein A in the formula (1) is any one of the tetravalent organic groups represented by the following formulas: [Chemical formula 3] 6. The thermosetting maleimide resin composition according to claim 1, wherein The number average molecular weight of the component (B) is 6,000 or less.

Citation Information

Patent Citations

  • LCP board cover material and LCP circuit board using the same

    JP2013074129A

  • Resin film, resin film with support, prepreg, metal-clad laminated sheet for high multilayer, and high multilayer printed wiring board

    JP2016131243A

  • Resin film, resin film with support, prepreg, metal-clad laminated sheet and multilayer printed wiring board

    JP2016131244A

  • Resin film for flexible printed wiring board and bonding sheet

    JP2018201024A

  • Polyamic acid for high-frequency substrate material, polyimide for high- frequency substrate material, polyimide film for high-frequency substrate material, polyimide molded product for high-frequency substrate material and high-frequency substrate

    JP2019104818A